2019
DOI: 10.1021/acs.organomet.9b00119
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Late-Stage ortho-C–H Bond Aroylation of Anilines Using 4-Methoxy-2-pyridinyl as a Removable Directing Group

Abstract: A synthetic methodology for the late-stage ortho-C–H bond aroylation of anilines with aryl aldehydes led to a variety of ortho-aroylated anilines by the use of palladium­(II) acetate, tert-butyl hydroperoxide, and 1,4-dioxane as the catalyst, oxidant, and solvent, respectively, is presented. An N-phenylpyridin-2-amine palladacycle was isolated and characterized by X-ray crystallography. Controlled experiments, radical trapping experiments, and the experiments of the kinetic isotope effect were undertaken to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…In 2019 Chu et al reported Pd(II)-catalyzed late stage ortho C-H bond acylation of anilines with aromatic aldehydes using 3methoxy-2-pyridinyl as removable directing group. 59 A wide substrate scope of differently substituted aryl aldehydes and N-protected anilines was explored to synthesize 26 monoacylated derivatives of aniline using Pd(OAc) 2 as catalyst and TBHP as oxidant (Scheme 25A). However, in few cases along with monoacylated aniline formation diacylated product was observed.…”
Section: -95%mentioning
confidence: 99%
“…In 2019 Chu et al reported Pd(II)-catalyzed late stage ortho C-H bond acylation of anilines with aromatic aldehydes using 3methoxy-2-pyridinyl as removable directing group. 59 A wide substrate scope of differently substituted aryl aldehydes and N-protected anilines was explored to synthesize 26 monoacylated derivatives of aniline using Pd(OAc) 2 as catalyst and TBHP as oxidant (Scheme 25A). However, in few cases along with monoacylated aniline formation diacylated product was observed.…”
Section: -95%mentioning
confidence: 99%
“…If the pyridine-directing group is linked to the aromatic ring through a heteroatom [ 7 ], it can be easily removed, so further transformations can be performed on the acylated compounds, significantly increasing the synthetic applicability of these transformations. Along these lines, the effect of the substitution on the pyridine ring was studied in the acylation of N -aryl-2-pyridinylamines 10 ( Scheme 3 ) [ 14 ].…”
Section: Acylation Of Arenesmentioning
confidence: 99%
“…The reaction was extended to a series of aldehydes obtaining 11 in moderate to good yields, although in most cases significant amounts of the diacylated products were also obtained. Both protecting groups could be efficiently removed to obtain amine 12 , which could also be transformed into an acridanone [ 14 ]. Besides the use of simple 2-pyridinyl, other related directing groups based on nitrogen coordination have been developed.…”
Section: Acylation Of Arenesmentioning
confidence: 99%
“…In 2019, Zhu's group disclosed a photoredox deoxygenative arylation of 2‐(phenylsulfonamido)benzoic acids generated in situ from anthranilic acids and arylsulfonyl chlorides (Scheme 1b) [10b] . In the same year, Wu's group described the formation of 2‐aminobenzophenones by the ortho ‐C−H bond aroylation of anilines containing a 4‐methoxy‐2‐pyridinyl directing group, which could be removed after two simple steps (Scheme 1c) [10c] . Although much progress has been achieved, the development of efficient methods for the synthesis of 2‐aminobenzophenones from novel starting materials is still highly desired.…”
Section: Introductionmentioning
confidence: 99%